PREGNANCY OUTCOMES DO INFLUENCE BY EXTREMES OF BODY MASS INDEX - Lubna Razzaq (Army Medical College Rawalpindi, 2021)
Objective: To investigate whether extreme of body mass index (BMI) is associated with pregnancy outcomes. Study Design: Retrospective cohort study. Place and Duration of Study: Hamdard University Hospital, Karachi, Pakistan, from Feb 2019 to Jan 2020. Methodology: We conducted a retrospective cohort study of 1000 women delivered in between February 2019 to January 2020. BMI is categorized into four groups according to the Asian-Pacific cutoff points as underweight (<18.5 kg/m2), normal weight (18.5–22.9 kg/m2), overweight (23–24.9 kg/m2), and obese (>25 kg/m2). Maternal outcomes measured were pre-eclampsia, gestational diabetes, delivery by cesarean section, instrumental delivery, anemia, postpartum hemorrhage and fetal outcome included small for gestational age and large for gestational age. Logistic regression model was used to adjust the confounder. Maternal outcomes were evaluated with relative risks and 95% confidence intervals. Results: In results, 13%, 54%, 22%, 9% and 2% were underweight, normal body mass index, overweight, obese and morbidly obese categories respectively. The gestational diabetes, pre-eclampsia, labour induction, frequency of cesarean section, post-partum hemorrhage increased linearly with increasing body mass index and expressed as adjusted odds ratio (95% confidence interval) respectively: 10.0 (95% CI 3.5, 28.7), 5.3 (95% CI 2.0, 14.1), 2.7 (95% CI 1.1, 6.8), 4.9 (95% CI 2.8–8.8), 2.5 (95% CI 0.31–20.6). The anemia and small for gestational age were found in underweight group with adjusted odd ratio2.47 (95% CI 1.6–3.6), 4.6 (95% CI 2.6, 8.1) respectively. Conclusion: Obese women are more prone to have maternal and fetal complication which includes preeclampsia, gestational diabetes, caesarean section rate, labor induction and macrosomic babies. Underweight women are not risk free for complica-tion as they are associated with anemia and small for gestational age.